Premature Mortality among People with Severe Mental Illness – New Evidence from Linked Primary Care Data - Lee, Sze Chim; John, Ann; McGregor, Joanna; Jones, Ian; Walters, James; Owen, Michael; O‘Donovan, Michael; del Pozo Banos, Marcos; Berridge, Damon; Lloyd, Keith (International Journal of Population Data Science, 2018)
Introduction Studies assessing premature mortality in people with severe mental illness (SMI) are often based in one setting, hospital (secondary care inpatients and/or outpatients) or community (primary care). This may lead to ascertainment bias. Objectives and Approach This study aimed to estimate standardised mortality ratios (SMRs) for all-cause and cause-specific mortality in people with SMI drawn from linked primary and secondary care populations compared to the general population. Standardised mortality ratios (SMRs) were calculated using the indirect method for a United Kingdom population of almost four million between 2004-2013. Results The all-cause SMR was higher in the cohort identified from secondary care hospital admissions (SMR: 2.9; 95% CI: 2.8-3.0) than from primary care (SMR: 2.2; 95% CI: 2.1-2.3) when compared to the general population. The SMR for the combined cohort was 2.6 (95% CI: 2.5-2.6). Solely hospital admission based studies may somewhat over-estimate premature mortality in those with SMI. However, there is no doubt this remains a major health inequality. Cause specific SMRs in the combined cohort were particularly elevated in those with SMI relative to the general population for ill-defined and unknown causes, suicide, and substance abuse, as well as a number of other causes. Conclusion/Implications The ability to combine cohorts electronically from primary and secondary care is more representative of the whole population. Comprehensive characterisation of mortality is important to inform policy and practice and to discriminate settings to allow for proportionate interventions to address this health injustice.